Cerebral Venous Sinus Thrombosis in Early Pregnancy : A Case Report - Akhter, Salma (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2019)
Cerebral Venous Sinus Thrombosis (CVST) in pregnancy is an uncommon condition and affects about 5 women per million. Actual etiology is difficult to confirm, a hypercoagulable state along with protein Sand C deficiency, hyperhomocystinaemia are the contributing factors. MRV like neuro imaging is the main stay of diagnosis. Treatment with Low molecular weight heparin throughout the pregnancy and post partum period can save the life of both mother and child. Chatt Maa Shi Hosp Med Coll J; Vol.18 (1); Jan 2019; Page 54-56